Pengaruh Persepsi dan Sikap Konsumen Terhadap Keputusan Pembelian Minuman Boba di Kota Metro - Resa Salsabila; Renata Lestari; Fikri Rizki Utama (Indonesia Economic Journal, 2025)
This study aims to analyze consumer behavior toward boba drinks in Metro City by testing the influence of Consumer Perception (X1) and Consumer Attitude (X2) on the Purchase Decision (Y). This quantitative, causal-associative research utilized Multiple Linear Regression analysis on data collected from a sample of 100 boba consumers selected via Purposive Sampling.The partial test results (t-test) showed that Consumer Perception (X) has a significant and positive effect on the Purchase Decision (Y) (Sig. 0.000), indicating that a good perception of product quality and service is the primary driver. Conversely, Consumer Attitude (X2) was found to have no significant effect, Sig. 0.798. However, the simultaneous test (F-test) confirmed that both Perception and Attitude significantly influence the Purchase Decision (Sig. 0.000). The Coefficient of Determination (R2) was 0.254, explaining 25.4% of the Purchase Decision variation. This study concludes that reinforcing positive consumer perception through improvements in quality and service is the most effective strategy for contemporary beverage businesses.